Are urbanization, biotic and social factors associated with the song frequency and song entropy attributes of three urban syntopic passerines? - Xhareni Díaz-Lezama; Alejandro Ariel Ríos-Chelén; Jorge Castellanos-Albores; Paula L. Enríquez (Avian Research)
Urban environments have challenging characteristics for bird acoustic communication. High levels of anthropogenic noise, as well as vegetation structure (e.g., in urban parks), can potentially affect the song frequency characteristics of several bird species. An additional factor such as the abundance of conspecific and heterospecific vocalizing birds may play an important role in determining the structure of bird songs. In this study, we analyzed whether noise levels, vegetation percentage, and abundance of conspecifics and heterospecifics influence the song characteristics of three syntopic songbird species: House Finch (Haemorhous mexicanus), Rufous-collared Sparrow (Zonotrichia capensis), and House Sparrow (Passer domesticus) living in urban sites. We recorded songs of these species and measured the peak frequency and entropy of their songs at 14 sites in the city of San Cristobal de Las Casas, Chiapas, Mexico. We found that the song peak frequency of House Finch and House Sparrow's songs was negatively related to the vegetation. The peak frequency of neither of the three species correlated with the average noise level. However, the abundances of conspecific and heterospecific were related to the peak frequency of the three species' songs. The entropy of the House Finch and House Sparrow songs was positively and negatively related, respectively, to noise levels. House Sparrow song entropy was negatively related to the percentage of vegetation. Song entropy of House Finches was negatively associated to conspecific and House Sparrow abundance. Song entropy of Rufous-collared Sparrows was positively related to conspecific abundance. In conclusion, the song peak frequency and song entropy of the three songbird species were differentially related to urban noise, vegetation, and conspecific and heterospecific abundance, suggesting these factors influence bird song characteristics.